Students’ Ability in Reading Narrative Text at The Eleventh Grade of SMAN 1 Masbagik in Academic Year 2023/2024 - Ilahi, M. Rifky Surya; Thohir, Lalu; Wardana, Lalu Ali; Elmiana, Dewi Satria (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study aim to analyze the ability of grade XI students at SMAN 1 Masbagik in reading narrative text. It is descriptive qualitative design. The participants in this study were 19 students from class XI-F7. The data were collected using a reading test and a questionnaire. The data obtained from the reading test were analyzed and calculated to determine the final score and identify the most difficult aspects of reading. Meanwhile, the data from the questionnaire were analyzed by reducing the data, displaying, and drawing conclusions. The results of this study indicate that out of 19 students, only three students scored in the very high category, six students scored high, three students scored medium, four students scored low, and three students scored very low. In addition, making inferences emerged as the most challenging reading aspect. Through an analysis of questionnaire responses, two prominent obstacles were identified: limited vocabulary knowledge and cognitive load. Many students faced difficulties in deciphering individual word meanings, thereby impeding their overall comprehension of texts. This study highlights the imperative for targeted strategies aimed at addressing these challenges to improve reading proficiency and academic achievement among students.